Optimized Random Vector Functional Link network to predict oil production from Tahe oil field in China; Oil & Gas Science and Technology - Revue d'IFP Energies nouvelles; Vol. 76 - Alalimi A. Ahmed; Pan Lin; Al-qaness Mohammed A. A.; Ewees A. A. Ahmed; Xiaoyan Wang; Mokhamed Elsaed (Mohamed Abd Elaziz) A. M. Akhmed Mokhamed (2021, 2021)
Title screen